Keanekaragaman Jenis Amfibi (Ordo Anura) di Kawasan Hutan Penelitian Bu’at So’e Kecamatan Mollo Selatan Kabupaten Timor Tengah Selatan Provinsi Nusa Tenggara Timur - Gaudensia Oktaraviani Tantap; Maria M. E. Purnama; Fadlan Pramatana (Wana Lestari, 2022)
Amphibians are an element of the ecosystem and part of the biodiversity that inhabits various habitats, thus becoming one of the groups of animal taxa commonly used as an indicator of environmental conditions. South Central Timor Regency has the potential as a natural habitat for amphibians because:has a temperature that ensures the growth and reproduction of amphibians. However, data on amphibian research is still very limited. This study aims to identify and identify diversity of amphibians of the order anura in the Bu'at-So'e Research Forest Area. The data collection method used in this study is a Visual Encounter Survey combined with a line transect. Data collection is done by making an observation path then repeated 3 times on each path. The data obtained were analyzed using the Shannon Wiener Index, species evenness, species richness, relative abundance, dominance and vegetation analysis. The results of the study found 134 individuals of amphibians consisting of 5 families and 7 species. The results showed that the species diversity index was in the medium category and the evenness, richness and dominance index were in the low category. This condition explains that, at the time the research was conducted, the habitat in the Bu'at-So'e Research Forest area was still guaranteeing the growth and reproduction of amphibians of the order Anura